2010
DOI: 10.3109/09637481003591608
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular receptor binding affinity of aqueous extracts fromAlliumspecies

Abstract: The known antihypertensive activity of Allium sativum cannot be correlated with binding to receptors involved in blood pressure regulation. However, aqueous extracts of the wild-type species of Allium show much higher affinities, warranting further explorations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…This study confirms the results obtained in previous researches [19,21,22]; in fact, these studies yet showed that the wild-type species of Allium, and in particular leaves and flowers, are more active and efficient in respect to garlic bulbs.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…This study confirms the results obtained in previous researches [19,21,22]; in fact, these studies yet showed that the wild-type species of Allium, and in particular leaves and flowers, are more active and efficient in respect to garlic bulbs.…”
Section: Resultssupporting
confidence: 95%
“…These results suggest further researches on spontaneous Allium species, in the past used as food or vegetables [20] and actually not much investigated. In effect these spontaneous Allium species resulted more active than A. sativum also in two successive studies by Nencini et al [21,22]. In the present study, we investigated the in vitro antioxidant activity of aged (up to 20 months) 15% hydroethanolic extracts of bulbs, leaves, flowers, bulblets and flower bulblets (these latter obviously only when present) of three Allium spontaneous species, previously studied on fresh material [19]: Allium neapolitanum Cyr., Allium roseum L., Allium subhirsutum L., and the in vitro antioxidant activity of aged 15% hydroethanolic extracts of bulbs and leaves of garlic (Allium sativum L.).…”
Section: Introductionmentioning
confidence: 87%
“…Nencini et al . [29] reported that A. sativum L. did not show high affinity for α 1 and α 2 receptors and showed a partial affinity for β 1 receptors, whereas wild-type Allium species presented a greater affinity for these receptors, in particular for β 2 receptors ( Allium neapolitanum and Allium subhirsutum species).…”
Section: Discussionmentioning
confidence: 99%
“…Known as garlic, it belongs to family Amaryllidaceae. It is known for its cardioprotective properties for milleniums (Fehri et al, 2011;Nencini et al, 2010;Ried et al, 2010) including vasorelaxant, antithrombotic and antiatherosclerotic by inhibiting platelet aggregation and plaque progression and by lowering cholestrol level in arterial cells (Koscielny et al, 1999;Orekhov et al, 1997). Seven dipeptides are found in allium extracts which are angiotensin converting enzyme (ACE)-inhibitors thus making it effective antihypertensive agent (Suetsuna et al, 1998).…”
Section: Allium Sativummentioning
confidence: 99%